Utilization of the Wondering, Exploring, and Explaining (WEE) Learning Model Assisted by GeoGebra to improve Understanding of Mathematical Concepts - Faradiba, Surya Sari; Walida, Sikky El; Alifiani, Alifiani; Sari, Fadhila Kartika; Ilmi, Yuli Ismi Nahdiyati; Khairunnisa, Gusti Firda; Syabrina, Dafa Atrian (International Journal of Research in Education, 2024)
This study aims to describe the application of the Geogebra-assisted Wondering, Exploring, and Explaining (WEE) learning model in improving the ability to understand mathematical concepts on lines and angles material at Junior High School of Darush Sholihin Batu in the 2022/2023 academic year. The study employs practical classroom action research, recruiting class VII-B as the research subjects. Interview guides, observation sheets, end-of-cycle test questions adapted to indicators of the ability to understand concepts, and field notes were the study's pilots for data collection. The findings showcased that the observation of teachers' and students' activities, the final cycle test completeness, and the interview results with happy students were boosted from cycles I to II. Furthermore, cycle II met the indicators of action success, indicating that the Geogebra-assisted Wondering, Exploring, and Explaining (WEE) learning model can improve the ability to understand mathematical concepts on lines and angles material at SMP Darush Sholihin Batu.